2016
DOI: 10.1016/j.ipej.2016.10.009
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mitral valve surgery on ventricular arrhythmia in patients with bileaflet mitral valve prolapse

Abstract: BackgroundBileaflet mitral valve prolapse (biMVP) is associated with frequent ventricular ectopy (VE) and malignant ventricular arrhythmia. We examined the effect of mitral valve (MV) surgery on VE burden in biMVP patients.MethodsWe included 32 consecutive patients undergoing MV surgery for mitral regurgitation secondary to biMVP between 1993 and 2012 at Mayo Clinic who had available pre- and post-operative Holter monitoring data. Characteristics of patients with a significant reduction in postoperative VE (gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 20 publications
0
40
0
2
Order By: Relevance
“…Ventricular ectopy burden was unchanged after mitral valve surgery. Only younger patients had a greater reduction in ventricular ectopy, suggesting that early surgical intervention could modify the underlying electrophysiologic substrate (29).…”
Section: Mitral Valve Repairmentioning
confidence: 99%
“…Ventricular ectopy burden was unchanged after mitral valve surgery. Only younger patients had a greater reduction in ventricular ectopy, suggesting that early surgical intervention could modify the underlying electrophysiologic substrate (29).…”
Section: Mitral Valve Repairmentioning
confidence: 99%
“…Mitral valve prolapse (MVP) is often associated with a mechanical myocardial and papillary muscle injury and fibrosis that can form a focus from which aberrant electrical potentials can be generated [9]. Furthermore, Naksuk et al showed that mitral valve surgery did not necessarily decrease the burden of ventricular arrhythmias and proposed that the arrhythmogenic substrate formed following longstanding MVP is frequently not reversed by valve replacement surgery [4]. The ECG taken prior to surgical repair in our case, showed frequent ventricular ectopic beats in a pattern of ventricular bigeminy, hinting to the development of an arrhythmogenic focus associated with long term mechanical strain related to MVP.…”
Section: Discussionmentioning
confidence: 99%
“…Structural heart disease increases the risk of developing an arrhythmia; the presence of mitral valve prolapse (MVP) is associated with an increased risk of ventricular arrhythmias and sudden death. Arrhythmias have been known to persist even after the replacement of the defective valve [4]. Although MVP is known to be arrhythmogenic [5], there is often a trigger that sets off the arrhythmogenic cascade.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the management of a young patient with mitral valve prolapse complaining of atypical chest pain, non specific palpitations or a Holter recording of ventricular premature beats (VPC) continues to engage a major challenge for the practicing physician. Moreover, many of us are aware of MVP patients who were timely diagnosed and apparently well treated but still died in a devastating way resulting from absence of appropriate risk stratification to help the burden of ventricular arrhythmias in patients with bileaflet MVP [18]. Thus, the role of MV surgery to reduce malignant arrhythmia is not conclusive and further studies will be needed before this could be advocated.…”
Section: Introductionmentioning
confidence: 99%